#TITLE_ALTERNATIVE# - PUSPITASARI (NIM 22308009); Pembimbing: Dr. Wawan Gunawan A. Kadir dan Dr. Susanti Alawiyah, ASRI
Surface time lapse microgravity method has been widely used in monitoring the density changes of reservoir fluid, although it still has limited vertical resolution. Alternatively, borehole gravity measurement has been developed in this research with derivation of gravity vertical gradient to produce better vertical resolution. A forward modeling code program has been created for gravity vertical gradient modeling for several models and then analyzed the anomaly response characteristics associated with amplitude, measurement interval in borehole, measurement distance from anomaly and body anomaly geometry. The result of synthetic modeling indicate that the boundary of anomaly body vertically and its depth can be identified clearly. In this case, top and base of body represented by zero gravity vertical gradient response value. For the borehole did not penetrate the top of anomaly body, the vertical gradient value will reach a maximum about 50 meters above the depth of anomaly body. Beside that, the borehole shifting from anomaly body will cause addition anomaly body thickness about 1.5 times for each meter with the farthest distance of 1000 meters. The combination between surface and limited borehole gravity data can be used therefore identification of anomaly body more optimal. As a survey recommendation, this vertical gradient method can be used because of vertical gradient log will be similar with density log.